Are thickened cranial bones and equal participation of the three structural bone layers autapomorphic traits of Homo erectus? - Antoine Balzeau (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Numerous studies have proposed different lists of morphological features to define the species of Homo erectus; among these, some are considered to be autapomorphic. The intention of this study is to discuss two of these possible autapomorphic traits: thickened cranial bones and equal participation of the three structural bone layers (inner and outer tables, diploe) in this thickening. This study brings new information concerning cranial vault thickness and structural composition in the mid-sagittal plane of some Asian Homo erectus. The Ngandong and Sambungmacan fossils, as well as the Zhoukoudian and Sangiran individuals, have cranial vault thickness values within the range of variation observed in our Homo sapiens comparative sample. Moreover, even if the frontal and sagittal keels in Homo erectus constitute a relief on the external cranial vault surface, they do not necessary correspond to a real thickening of the underlying bone. The diploic layer principally contributes to their internal composition. Similarly, the diploe constitutes the greatest part of the total vault thickness along the mid-sagittal plane, particularly in the frontal and occipital tori, in the analysed fossils of this extinct species. Finally, our results show that Homo erectus individuals have cortical tables as well as diploe variation and distribution patterns similar to anatomically modern Homo sapiens. Therefore, the two tested autapomorphic traits for Homo erectus can no longer be considered as valid. L’épaisseur importante de la voûte crânienne et l’hyperossification de la table compacte externe, deux caractères considérés comme autapomorphiques pour l’espèce Homo erectus, sont étudiés. La variation de l’épaisseur et sa constitution interne ont été analysées le long du plan sagittal médian chez des représentants de l’espèce Homo erectus. Les fossiles de Ngandong, Sambungmacan, Sangiran et Zhoukoudian étudiés ont dans l’ensemble des valeurs d’épaisseur crânienne qui se situent dans la variabilité de notre échantillon d’Hommes anatomiquement modernes. De plus, les fossiles attribués à Homo erectus et Homo sapiens partagent le même schéma de distribution de l’épaisseur crânienne et des tables osseuses le long du plan sagittal médian. Si la carène sagittale chez Homo erectus constitue un relief osseux externe, elle ne correspond pas nécessairement à un réel épaississement de l’os sous-jacent, ni à celui de la table compacte externe comme admis jusque là. Le diploé en compose la majeure partie comme cela est observé sur les torus frontal et occipital transverse. Les caractères testés ne sont donc pas des autapomorphies de l’espèce Homo erectus.